1977
DOI: 10.2190/weef-n0hd-0cq5-18ty
|View full text |Cite
|
Sign up to set email alerts
|

Widow's Grief: The Impact of Age and Mode of Death

Abstract: Two variables (age and mode of death) were tested to discover if they could predict the intensity of the grief reaction. It was hypothesized that widows who experienced anticipatory grief would resolve the bereavement crisis in an easier manner than those experiencing the sudden death of a mate, and that younger widows would experience the effects of acute grief to a greater degree than older widows. Information was obtained by a questionnaire from eighty widows bereaved six to nine months. They were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 38 publications
11
60
0
Order By: Relevance
“…This study went some way towards quantifying psychological distress in the face of a threatened loss, and the results tend to support the concept of anticipatory grief. Ball (1977) related grief reactions to the duration of terminal illness in young, middle-aged and elderly patients. She concluded that 'anticipatory grief is a mitigating influence on postmortem grief'.…”
Section: Anticipatory Griefmentioning
confidence: 99%
“…This study went some way towards quantifying psychological distress in the face of a threatened loss, and the results tend to support the concept of anticipatory grief. Ball (1977) related grief reactions to the duration of terminal illness in young, middle-aged and elderly patients. She concluded that 'anticipatory grief is a mitigating influence on postmortem grief'.…”
Section: Anticipatory Griefmentioning
confidence: 99%
“…These comprise: the women's age (Ball, 1977); marital status and educational level (Rådestad et al, 1996); emotional relations/support (Kurz et al, 1997); the women's participation in the care of her partner (Häggmark et al, 1991); intensity of religious faith; treatment for mental health problems prior to the disease/ loss; the site and duration of the patient's illness; and the duration of time the woman was aware of her partner's impending death (awareness time) (identified in this data set).…”
Section: Methodsmentioning
confidence: 99%
“…8 The implications are that for young widows, widowhood is not merely a state of mourning, but rather a process of adaptation which is largely a process of identity reconstruction, as premature loss results in identity discontinuity. 9 It is this well-documented loss of identity occasioned by the advent of young widowhood and the subsequent need to rebuild the self which makes the young widow memoir of particular interest to scholarly examination of narrative identity construction.…”
Section: The Young Widow Memoirmentioning
confidence: 99%